Characterization of Ge1-x-ySixSny Ternary Alloy Surfaces and Ni/Ge1-x-ySixSny Bilayer Reactions by X-Ray Techniques. Issue 1770 (2015) - Grzybowski, Gordon J.; Kiefer, Arnold; Claflin, Bruce
ABSTRACT: Interest in next generation devices that integrate photonic and electronic functionality is focused on extending the capability of existing group IV material systems while maintaining compatibility with existing processing methods and procedures. One such class of materials which has been recently developed, Ge1-x-y Six Sny ternary alloys, is being investigated for integrated Si photonics, solar cell materials, telecommunication applications, and for IR photodetectors. These alloys afford the opportunity to decouple the band gap energies and lattice constants over a wide range of values, potentially yielding direct and indirect character that can be coupled with a variety of different substrates dependent on composition. In the present work, we report X-ray photoelectron spectroscopy (XPS) characterization of Ge1-x-y Six Sny alloys grown by gas-source molecular beam epitaxy (GS-MBE) and investigate Ni- Ge1-x-y Siy Sny bilayer reactions with x-ray diffraction (XRD). The surface oxidation of samples stored in ambient conditions were measured with XPS. High resolution spectra showed chemical shifts of Ge, Si and Sn peaks consistent with Ge-O, Si-O and Sn-O bond formation. Depth profiling indicates a homogeneous composition throughout the bulk of the sample with surface oxidation confined to the top few nanometers. A highly tin-enriched layer was indicated at the surface of the material, while silicon was observed to be either enriched or depleted at the surface depending on the sample. To study the interaction of the ternary with an ohmic contact commonly used in device fabrication processes today, nickel layers 30 nm thick were evaporated onto the alloys and were annealed in nitrogen up to 400 ° C for periods as long as 1 hour. The XRD data show that the Ni2 (Ge1-x-y Six Sny ) phase forms first followed by Ni(Ge1-x-y Six Sny ).